O critério a ser adotado para a definição da vítima do feminicídio - Machado, Amanda Backes (Universidade do Vale do Rio dos Sinos, 2018)
Nowadays, it has been debated by the juridical doctrine and the jurisprudence who may be victim of domestic and familiar violence, especially in the crime of feminicide, i. e., who may be considered woman. There are three criteria that try to stablish baselines to check who is able to be considered woman. The first of them, it’s biological, explaining that only the female born one may be known as woman. The second one, concerning to the psychological part, it’s when a person is born with a certain sex and feels like the opposite one. And, according to the third criteria, the juridical one, it can only be considered woman the person who has its name and gender enrolled in the Civil Registry, as female. Analyzing it, by the juridical criteria optic, transsexuals, characterized as being people who feel themselves as the opposite sex, calling for changes in their bodies aiming the sex they feel like, may be feminicide victims. Yet concerning to the transvestites, as the people who feel like the opposite sex, but have not modified their bodies, it has prevailed the comprehension that they cannot be victims of the feminicide.
Keywords: Transexuais; Travestis; Feminicídio; Critérios; Mulher; Transsexuals; Transvestites; Feminicide; Criteria; Woman